Framing of Climate Change in Pakistani YouTube Content: A Content Analysis of Climate-Related Videos Across Selected Communication Channels - Malik, Nasir Iqbal; Arif, Maryum; Tariq, Iqra; Khan, Ammar Riaz; Ramazan, Mian Muhammad (Regional Lens, 2025)
This paper provides information that digital media has a huge impact on public perceptions and is essential for effective climate communication and advocacy in Pakistan. Despite the fact that Pakistan produces very little global carbon emissions, it faces the highest climate change risks. This research investigated the addressed practices of prominent communication platforms including national broadcasters, international news organizations, and NGOs to study how they present the climate change crisis to Pakistani audiences. A quantitative content analysis was conducted on 12 YouTube videos from the most relevant channels. These channels include DW, BBC, Geo News and WWF Pakistan. The analytical framework is resultant from media framing theory. It used exactly four analytical frames: Adaptation/Solution, Disaster/Impact, Causal Attribution and Livelihood/Economic. The investigation revealed that Disaster/Impact and Livelihood/Economic frames dominated the content. Videos give a talk on glacial lake outburst floods and monsoon flooding used emotionally convincing images to carry direct threats. As demonstrated by SAMAA TV and FRANCE 24 reporting. Connecting climate change to tangible socioeconomic influences. Such as distraction to old-style Karez irrigation systems and agricultural losses in mango farming. Channels like Geo News and BBC News hired this framing method obviously Pakistan is often unfairly portrayed as weak, mainly due to Western and Chinese industrial influence, as seen on channels like MIRROR NOW. However, these frames stored significantly lesser engagement points. The algorithmic instruments of YouTube seem to rank instant disaster stories over solution-oriented content. The practice of vernacular language verified momentous. Local language content improved the human-interest dimension.